2019
DOI: 10.1002/humu.23780
|View full text |Cite
|
Sign up to set email alerts
|

The TALE homeodomain of PBX1 is involved in human primary testis‐determination

Abstract: Human sex‐determination is a poorly understood genetic process, where gonad development depends on a cell fate decision that occurs in a somatic cell to commit to Sertoli (male) or granulosa (female) cells. A lack of testis‐determination in the human results in 46,XY gonadal dysgenesis. A minority of these cases is explained by mutations in genes known to be involved in sex‐determination. Here, we identified a de novo missense mutation, p.Arg235Gln in the highly conserved TALE homeodomain of the transcription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…Interestingly, the second affected sibling (II‐5; 46, XY) presented here showed complete sex reversal of both internal and external organs, without any signs of male gonad development (no streak gonad). In line with earlier reports (Eozenou et al, ; Slavotinek et al, ), the phenotypic heterogeneity among patients carrying the same mutation indicates a limited genotype–phenotype correlation, possibly influenced by factors such as gender, genetic modifiers, or skewed gene expression.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Interestingly, the second affected sibling (II‐5; 46, XY) presented here showed complete sex reversal of both internal and external organs, without any signs of male gonad development (no streak gonad). In line with earlier reports (Eozenou et al, ; Slavotinek et al, ), the phenotypic heterogeneity among patients carrying the same mutation indicates a limited genotype–phenotype correlation, possibly influenced by factors such as gender, genetic modifiers, or skewed gene expression.…”
Section: Discussionsupporting
confidence: 87%
“…Genital abnormalities are commonly reported in male patients with PBX1 mutations (10/14), with the phenotypic spectrum ranging from cryptorchidism to partial development of female internal and/or external genitalia (Alankarage et al, ; Eozenou et al, ; Kia et al, ; Riedhammer et al, ; Slavotinek et al, ; Le Tanno et al, ). Interestingly, the second affected sibling (II‐5; 46, XY) presented here showed complete sex reversal of both internal and external organs, without any signs of male gonad development (no streak gonad).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variant is located in a highly conserved TALE homeodomain of the protein, as opposed to previously described variants that are located in the consensus splice site, potentially explaining the different phenotype [72,73]. In vitro studies of cellular location showed that the mutated p.Arg235Gln PBX1 protein was unable to correctly localize into the nucleus and also had an impaired biological activity, as its physical interaction with two proteins known to be involved in testis determination (EMX2 and CBX2) were abolished [74]. This data suggests that specific variants located in the TALE homeodomain of PBX1 are a novel cause of human 46,XY DSD.…”
Section: Pbx1 and Cbx2: Gene Interactions That Promote Testis Developmentioning
confidence: 70%
“…In humans, deleterious variants involving PBX1 were previously associated with congenital anomalies of the kidney and urinary tract, but not with DSD [72,73]. PBX1 has been implicated in human testicular development after the identification of a single de novo heterozygous variant (p.Arg235Gln) in a 46,XY GD patient with normal kidneys and radiocubital synostosis [74]. This variant is located in a highly conserved TALE homeodomain of the protein, as opposed to previously described variants that are located in the consensus splice site, potentially explaining the different phenotype [72,73].…”
Section: Pbx1 and Cbx2: Gene Interactions That Promote Testis Developmentioning
confidence: 99%